2022
DOI: 10.1017/s0950268822001297
|View full text |Cite
|
Sign up to set email alerts
|

Comparative symptomatology of infection with SARS-CoV-2 variants Omicron (B.1.1.529) and Delta (B.1.617.2) from routine contact tracing data in England

Abstract: Symptoms are currently used as testing indicators for SARS-CoV-2 in England. In this study, we analysed national contact tracing data for England (NHS Test and Trace) for the period 1 December to 28 December 2021 to explore symptom differences between the variants, Delta and Omicron. We found that at least one of the symptoms currently used as indicators (fever, cough, and loss of smell and taste) were reported in 61.5% of Omicron cases and 72.2% in Delta cases, suggesting that these symptoms are less predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
(19 reference statements)
1
11
0
Order By: Relevance
“…Recent studies have shown changing symptomatology of COVID‐19 infection, with each virus variant “wave” demonstrating varying clinical features 7‐9 . Though considered a disease‐defining symptom, decreasing incidence of olfactory disturbance was demonstrated with data from the powerful N3C database 3 —findings corroborated by subsequent studies using differing means 4,10 . The current data indicates a further, precipitous drop in rates of olfactory loss with recent Omicron variants.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Recent studies have shown changing symptomatology of COVID‐19 infection, with each virus variant “wave” demonstrating varying clinical features 7‐9 . Though considered a disease‐defining symptom, decreasing incidence of olfactory disturbance was demonstrated with data from the powerful N3C database 3 —findings corroborated by subsequent studies using differing means 4,10 . The current data indicates a further, precipitous drop in rates of olfactory loss with recent Omicron variants.…”
Section: Discussionsupporting
confidence: 70%
“…This study has several limitations. First, rates of smell loss reported for all variant time periods are well below previously reported rates 10,11 . As with any database, N3C is dependent on coding, which relies on clinicians to both query about and document chemosensory changes.…”
Section: Discussionmentioning
confidence: 67%
“…Since then, this variant has rapidly replaced Delta as the dominant variant of concern globally, further producing descendent lineages that include BA.1, BA.2, BA.3, BA.4, and BA.5 [ 29 , 30 ]. The symptomatology of this variant also differed drastically from the previous Delta variant, with the three cardinal symptoms of fever, cough, and loss of smell and taste only being reported in 61.5% of Omicron cases compared to 72.2% of Delta cases [ 31 ]. Furthermore, when analyzing the percent of cases reporting anosmia and dysgeusia, these symptoms were found to be less common among those with Omicron (13.4%) infections compared to Delta (33.7%) infections ( p < 0.001).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, when analyzing the percent of cases reporting anosmia and dysgeusia, these symptoms were found to be less common among those with Omicron (13.4%) infections compared to Delta (33.7%) infections ( p < 0.001). [ 31 ]…”
Section: Methodsmentioning
confidence: 99%
“…2). Twenty-two studies were from populations primarily of European ancestry [8,32,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59], eight studies on East Asians [60][61][62][63][64][65][66][67], three studies on South Asians [68][69][70], three studies on Latinos [71][72][73], four studies on populations in Africa [74][75][76][77], and one study from West Asia (Turkey [78]). The location of studies, with the prevalence indicated by the color intensity, and the cohort size indicated by the size of the circles, shows that Western countries report the highest prevalence, while studies from East Asia and Africa report the lowest prevalence (Fig.…”
Section: Properties Of Studiesmentioning
confidence: 99%